AGE OF FORMATION OF APOCARBONATE METASOMATITES OF THE SHARYZHALGAI UPLIFT OF THE SIBERIAN CRATON BASEMENT, SOUTHWESTERN BAIKAL REGION: U-PB BADDELEYITE AND ZIRCON DATINGS - Levitskii V.I.; Sal'nikova E.B.; Kotov A.B.; Yakovleva S.Z.; Kovach V.P.; Plotkina Yu.V.; Reznitskii L.Z.; Barash I.G.; Mel'nikov A.I. (My University, 2004)
Together with geological data, results of geochronological investigations indicate that apocarbonate metasomatites in the eastern part of the Sharyzhalgai Uplift of the Siberian Craton formed during an Early Proterozoic, presumably short-term, metamorphic event (with a duration of not more than 15-19 Ma, within measurement errors). Obtained datings are consistent with geopetrological data on the subsequent formation of metasomatites of the migmatitic and magmatic stages, although, judging from similar age estimates, the time interval between these processes was insignificant. In addition, the obtained geochronological data support the recognition of magnesian skarns of the magmatic stage in high-grade Precambrian metamorphic complexes On the whole, the first experience of UPb baddeleyite dating of apocarbonate metasomatites makes it possible to consider them as unique objects that can be used not only for direct dating of metamorphic events, but also for approximate estimation of their duration.